A MULTILEVEL USER VALIDATION FRAMEWORK FOR ACCESSING CLOUD SERVICES - Gadde, Swetha; K, Janaki (The journal of contemporary issues in business and government, 2021)
Cloud computing is a paradigm that offers enormous advantages to cloud users for example, huge memory, adaptable processing abilities, security to the data and boundless registering capabilities. To utilize the maximum capacity of Cloud computing, information is moved, handled and stored by Cloud Service Providers (CSP). Be that as it may, information owners are suspicious to put their information in cloud that is outside their own control. The main issue with Cloud computing is the manner by which to provide the security and protection of cloud user information being prepared and additionally stored in a Cloud computing condition. With regards to cloud information assurance, the techniques utilized can be fundamentally the same as ensuring information inside a conventional server group. To perform user validation for accessing cloud services, a strong cryptography method is introduced along with a multi factor verification process. Moving information into the cloud implies that the clients have less authority over their information, this implies the cloud clients must believe the CSP to secure the information from both outside and inside attacks. In the proposed work, a Multi Level User Authentication (MLUA) framework is introduced for accessing cloud services. The unauthorized users are not allowed to access cloud resources. The cloud user, data owner and cloud service providers are involved in multi factor authentication. The CSP will generate a Digital Unique Authentication Identity (DUAI) number along with general verification for undergoing multi level verification process. The proposed method is compared with the traditional methods and the results show that the proposed method is better in performance and accuracy in identification of valid cloud users.